Encourage land use in land resources diversification - Мahsudov Muhammadbek Dilshodbek ugli; Khakimova Shokhidakhon Abdilxodievna (Universitas Muhammadiyah Sidoarjo, 2020)
The article mentions that it is important to encourage the use of land in the process of diversification of land use. The incentive function is a mechanism of economic impact for land users to make effective use of land.